1992
DOI: 10.1038/hdy.1992.125
|View full text |Cite
|
Sign up to set email alerts
|

Proximal chiasmata induce non-disjunctional orientation of Robertsonian trivalents in a grasshopper

Abstract: The relationship between the symmetry of the meiotic configuration and the type of meiotic orientation (disjunctional and non-disjunctional) in Robertsonian trivalents of Dichroplus pratensis (Melanoplinae, Acrididae) was analysed. The results indicate, first, that neither chromosomal size nor the relation between the length of the chromosomes involved in each fusion are important factors for the determination of the orientation. Second, chiasmata localization, which in turn determines effective inter-centrome… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
23
1

Year Published

1994
1994
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(24 citation statements)
references
References 30 publications
(64 reference statements)
0
23
1
Order By: Relevance
“…Rb fusions have very different consequences on recombination than B-chromosomes or inversions although some of their effects are comparable to the latter. In D. pratensis, Rb fusions affect recombination in two ways (Bidau, 1990;Mirol and Bidau, 1992;Bidau and Martí, 1995;Martí and Bidau, 1995): first -interchromosomal recombination is decreased because of the reduction of elements that are transmitted independently; second -each fusion affects intrachromosomal recombination by reducing chiasma frequency and shifting chiasmata to distal positions of chromosomes, generating recombination-free pericentromeric regions and potential linkage disequilibria. Thus, standard marginal populations not only have higher recombination indices but also a completely different pattern of chiasma localization where interstitial regions are relatively free of crossing-over.…”
Section: Bivalentmentioning
confidence: 99%
“…Rb fusions have very different consequences on recombination than B-chromosomes or inversions although some of their effects are comparable to the latter. In D. pratensis, Rb fusions affect recombination in two ways (Bidau, 1990;Mirol and Bidau, 1992;Bidau and Martí, 1995;Martí and Bidau, 1995): first -interchromosomal recombination is decreased because of the reduction of elements that are transmitted independently; second -each fusion affects intrachromosomal recombination by reducing chiasma frequency and shifting chiasmata to distal positions of chromosomes, generating recombination-free pericentromeric regions and potential linkage disequilibria. Thus, standard marginal populations not only have higher recombination indices but also a completely different pattern of chiasma localization where interstitial regions are relatively free of crossing-over.…”
Section: Bivalentmentioning
confidence: 99%
“…A complex system of eight polymorphic and polytypic Robertsonian (Rb) fusions that involves the six large autosomes (L1 -L6) is superimposed upon the standard telocentric chromosome complement (2n = 18 + X$, 18 + XX?). Meiotic studies of a large number of Argentinian populations, demonstrated that the Rb fusions strongly affect chiasma frequency and distribution and thus, potential genetic recombination and meiotic orientation and segregation (BIDAU 1990(BIDAU , 1991(BIDAU , 1993(BIDAU , 1996BIDAU et al 1991;MIROL and BIDAU 1991, 1992, 1994TOSTO and BIDAU 1991; MARTI 1995, 1998; MART^ and BIDAU 1995, 1998). An adaptive role of the fusions as potential reservoirs of coadapted supergenes through the creation of recombination-free chromosomal regions, has been pro-* Both authors are affiliated with the Consejo Nacional de Investigaciones Cientificas y Tknicas, Argentina.…”
mentioning
confidence: 99%
“…They are affected by the intercentromeric distance which is determined by the chiasma frequency and location (Rickards 1983). Thus, distal chiasmata in large chromosomes would render considerable intercentromeric distances avoiding adjacent centromeres which are more susceptible to orientation to the same pole (Mirol and Bidau 1992) .…”
Section: Influence Of Spontaneous Fusions On Chiasma Conditionsmentioning
confidence: 99%
“…Stable chromosome polymorphisms usually involve rearrangements which segregate disjunctionally at anaphase I without affecting the fertility of the carriers. In particular, polymorphic centric fusions exhibiting efficient segregation are often associated with a reduction in the number of chiasmata in the involved pairs and an increase in distal distribution of them with respect to basic homozygotes (White 1973, Hewitt 1979, Rickards 1983, Colombo 1989, 1993, Bidau 1990, Mirol and Bidau 1992. These characteristics seem to favour alternate oriented trivalents through an increase of intercentromeric distances (Rickards 1983).…”
mentioning
confidence: 99%